2001
DOI: 10.1073/pnas.121006298
|View full text |Cite
|
Sign up to set email alerts
|

Rad52 forms DNA repair and recombination centers during S phase

Abstract: Maintenance of genomic integrity and stable transmission of genetic information depend on a number of DNA repair processes. Failure to faithfully perform these processes can result in genetic alterations and subsequent development of cancer and other genetic diseases. In the eukaryote Saccharomyces cerevisiae, homologous recombination is the major pathway for repairing DNA double-strand breaks. The key role played by Rad52 in this pathway has been attributed to its ability to seek out and mediate annealing of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

25
423
1
3

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 426 publications
(457 citation statements)
references
References 68 publications
(54 reference statements)
25
423
1
3
Order By: Relevance
“…To examine the possibility that dia2 cells accumulate spontaneous DNA damage, we used a Rad52-YFP reporter strain. Rad52 is involved in recombinational repair and has been shown to localize to discrete nuclear foci when cells are treated with DNA-damaging agents (Lisby et al, 2001). We generated a dia2 Rad52-YFP strain and examined the cells using fluorescence microscopy.…”
Section: Dia2 Binds Replication Originsmentioning
confidence: 99%
See 1 more Smart Citation
“…To examine the possibility that dia2 cells accumulate spontaneous DNA damage, we used a Rad52-YFP reporter strain. Rad52 is involved in recombinational repair and has been shown to localize to discrete nuclear foci when cells are treated with DNA-damaging agents (Lisby et al, 2001). We generated a dia2 Rad52-YFP strain and examined the cells using fluorescence microscopy.…”
Section: Dia2 Binds Replication Originsmentioning
confidence: 99%
“…We generated a dia2 Rad52-YFP strain and examined the cells using fluorescence microscopy. A deletion mutant of the checkpoint kinase Mec1 (suppressed by deletion of the ribonucleotide reductase inhibitor Sml1) was used as a positive control (Lisby et al, 2001). The dia2 mutant showed an increased number of Rad52-YFP foci over WT.…”
Section: Dia2 Binds Replication Originsmentioning
confidence: 99%
“…In yeast, distinct Rad52 foci that undoubtedly contain multiple protein rings form under conditions that result in DSBs, e.g. during meiosis and in S phase mitotic cells, and following exposure to ␥-irradiation (27). Also, co-localization of RAD52 group proteins, including Rad51, Rad52, and Rad54, is observed following DNA damage in mammalian cells (28 -31).…”
mentioning
confidence: 99%
“…Also, co-localization of RAD52 group proteins, including Rad51, Rad52, and Rad54, is observed following DNA damage in mammalian cells (28 -31). Therefore, it appears that the ability of Rad52 to form higher order oligomeric complexes may be important to its function in promoting homologous recombination, and it has been suggested that such complexes may be required as an early step in the efficient catalysis of DNA repair via homologous recombination (27). Given the domain structure of the HsRad52 protein it may be that higher order oligomers of the protein are used in promoting complex formation among repair proteins and DNA through simultaneous interaction with multiple components.…”
mentioning
confidence: 99%
“…Nuclear foci formed by fluorescent protein-tagged Rad52 have been widely used to assess the level of DNA damage in live cell imaging analysis (Lisby et al 2001;Du et al 2003). Unlike phospho-H2A(X), which is not found at the immediate vicinity of DSBs due to end resection (Shroff et al 2004), Rad52 is recruited to single-strand DNA (ssDNA) exposed by resection, in a replication protein A (RPA)-dependent manner (Lisby et al 2004).…”
mentioning
confidence: 99%